DIFFERENTIAL DIAGNOSIS OF COMMUNITY-ACQUIRED PNEUMONIA FROM COVID-19 BY COMPUTED TOMOGRAPHY - PASHA , N; AKRAM , MN; WAQAR , N; PASHA , K (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted on data collected from tertiary Care Hospitals from January 2020 to May 2021 to compare CT manifestations and clinical features of COVID-19 with CAP and evaluate the diagnostic accuracy of CT in patients with COVID-19 and CAP. The study included one hundred sixty patients with COVID-19 and 115 with CAP diagnosed during the same time. Clinical data and CT images of the participants were collected. Results showed that 134 (84.3%) patients in the COVID-19 group had ground glass opacities on CT scans. In the COVID-19 group, the typical early presentation was single or multiple small round lesions. 51 (31.8%) patients had small lesions, and 83 (51.8%) had large patches, areas of fusion, or density shadows with spots. In the CAP group, 69 (60%) patients had consolidation, and 45 (39.1%) had ground glass shadows. There was a significant difference in density between both groups (P <.001). Of observed imaging and clinical manifestations, ground glass shadows, number of leukocytes, and age factor are clinically significant in diagnosing COVID-19. In the CAP group, major characteristics were the thickening of the bronchial wall, accumulation of textures and fibrous cords, and consolidated lung lesions. In COVID-19, common imaging manifestations of GGO and consolidation. Clinically, a CT scan should be used along with history and examination for early and accurate diagnosis of COVID-19.